Osteopenia in Puerto Ricans with Crohn's Disease - Chinea, Betty; Rosa, Arnaldo; Oharriz, Juan J.; Ramírez, Margarita; Haddock, Lillian; Pérez, Cynthia; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2013)
see manuscript